ZDHHC15 as a candidate gene for autism spectrum disorder. Issue 4 (23rd December 2022) - Casellas‐Vidal, Dolors; Mademont‐Soler, Irene; Sánchez, Joana; Plaja, Alberto; Castells, Neus; Camós, Maria; Nieto‐Moragas, Javier; del Mar García, Maria; Rodriguez‐Solera, Celia; Rivera, Helena; Brunet, Joan; Álvarez, Sara; et al.
Abstract: The phenotypic repercussion of ZDHHC15 haploinsufficiency is not well‐known. This gene was initially suggested as a candidate for X‐linked mental retardation, but such an association was later questioned. We studied a multiplex family with three members with autism spectrum disorder (ASD) by array CGH, karyotype, exome sequencing and X‐chromosome inactivation patterns. Medical history interviews, cognitive and physical examinations, and sensory profiling were also assessed. The three family members with ASD (with normal cognitive abilities and an abnormal sensory profile) were the only carriers of a 1.7 Mb deletion in the long arm of chromosome X, involving: ZDHHC15, MAGEE2, PBDC1, MAGEE1, MIR384 and MIR325 . The normal chromosome X was preferentially inactivated in female carriers, and the whole exome sequencing of an affected family member did not reveal any additional genetic variant that could explain the phenotype. Thus, in the present family, ASD segregates with a deletion on chromosome X that includes ZDHHC15 . Considering our results together with gene data (regarding function, expression, conservation and animal/cellular models), ZDHHC15 is a candidate gene for ASD. Emerging evidence also suggests that this gene could be associated with other neurodevelopmental disorders, with incomplete penetrance and variable expressivity.